Níveis de resveratrol, outros compostos fenólicos e ocratoxina A em vinhos tintos de diferentes origens - Abreu, Priscilla Silva de (2017)
Ochratoxin A (OTA) has been frequently found as a contaminant of grapes, grape juice and wine, and is considered one of the most harmful mycotoxins to human health. However, there is a growing interest in these beverages, due to the benefits promoted by the phenolic compounds present in the grape. Resveratrol is the compound most reported to present this benefits, being associated mainly with cardiovascular health improvement. The toxin production, as well as resveratrol, is influenced by several common factors, such as temperature, ultraviolet radiation, excessive irrigation, the presence of contaminating microorganisms and a substrate composition. In this context, this study was carried out with the objective of evaluating the occurrence of OTA and resveratrol (total, cis and trans) in red wines Cabernet sauvignon cv., as well as to evaluate the correlation between the two compounds. OTA and resveratrol quantification in wine samples was performed by high performance liquid chromatography (HPLC) method, with fluorescence detection. A small part of the analyzed samples (5%) presented contamination by Ochratoxin A, however, the contamination is relatively low, with values from 0.44 μg / L to 0.161 μg / L. The presence of resveratrol was observed in 87,5% of analyzed wines, being mostly associated with the trans-resveratrol content, since few samples presented cis isomer values, proving their high instability. No correlation was observed between levels of ochratoxin A, total resveratrol, trans-resveratrol and cis-resveratrol. The study‟s results show that the consumption of the evaluated samples does not imply a risk to the health of the consumer, since the presence of OTA was not observed in most of the wines analyzed and, in those where it was detected, the levels of contamination were very low, thus not compromising the product safety. Other studies on the incidence of OTA and resveratrol, as well as the correlation of these two, compounds are necessary to allow a better understanding of the factors that contribute significantly to their incidence in wines in order to minimize the potential risk of the presence of the toxin and potentiate the beneficial effects of resveratrol.